Pengaruh Persepsi Mahasiswa Akuntansi terhadap Penerapan Standar Akuntansi Keuangan di Universitas 17 Agustus 1945 Surabaya - Siti Nurul Hidayati; Hwihanus Hwihanus (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
This study aims to analyze accounting students' perceptions of the application of Financial Accounting Standards (FAS) at the University of 17 August 1945 Surabaya and the effect of these perceptions on their readiness to apply FAS in the professional world. This study uses a descriptive qualitative approach with data collection techniques through questionnaires distributed to accounting students who have received courses related to SAK. The results showed that the majority of students have a good understanding of SAK, but there are some who do not fully understand the standard. The role of lecturers proved significant in helping students understand and apply SAK correctly. The application of SAK in accounting education is considered important by the majority of students, because it supports their readiness to face the world of work. The results of this study are expected to provide input for the development of accounting education curriculum to be more effective in instilling understanding and application of SAK.